Effective coverage of curative child health services in Ethiopia: analysis of the Demographic and Health Survey and Service Provision Assessment survey - Lenka Benova; Anteneh Asefa; Alemnesh H Mirkuzie; Tsegaye Gebremedhin Haile (BMJ Open, 2024)
Objectives Despite a remarkable decline, childhood morbidity and mortality in Ethiopia remain high and inequitable. Thus, we estimated the effective coverage of curative child health services in Ethiopia.Design We conducted a cross-sectional analysis of data from the 2016 Ethiopia Demographic and Health Survey (DHS) and the 2014 Ethiopia Service Provision Assessment Plus (SPA+) survey.Setting Nationally representative household and facility surveys.Participants and outcomes We included a sample of 2096 children under 5 years old (from DHS) who had symptoms of one or more common childhood illnesses (diarrhoea, fever and acute respiratory infection) and estimated the percentage of sick children who were taken to a health facility (crude coverage). To construct a quality index of child health services, we used the SPA+ survey, which was conducted in 1076 health facilities and included observations of care for 1980 sick children and surveys of 1908 mothers/caregivers and 5328 health providers. We applied the Donabedian quality of care framework to identify 58 quality parameters (structure, 31; process, 16; and outcome, 11) and used the weighted additive method to estimate the overall quality of care index. Finally, we multiplied the crude coverage by the quality of care index to estimate the effective coverage of curative child health services, nationally and by region.Results Among the 2096 sick children, only 38.4% (95% CI: 36.5 to 40.4) of them were taken to a health facility. The overall quality of care was 54.4%, weighted from structure (30.0%), process (9.2%) and outcome (15.2%). The effective coverage of curative child health services was estimated at 20.9% (95%CI: 19.9 to 22.0) nationally, ranging from 16.9% in Somali to 34.6% in Dire Dawa regions.Conclusions System-wide interventions are required to address both demand-side and supply-side bottlenecks in the provision of child health services if child health-related targets are to be achieved in Ethiopia.